PENGARUH KESADARAN ETIS DAN PERTIMBANGAN ETIS TERHADAP WHISTLEBLOWING: EMOSI SEBAGAI VARIABEL PEMODERASI - Eva Fadilah; Fauziah Aida Fitri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study had a purposed to evaluate the effect of ethical awareness, ethical judgement on whistleblowing with emotion as a moderating variable on employees of PT PLN (Persero) in the cities of Banda Aceh and Aceh Besar. The sample taking by non-probability sampling method and purposive sampling. It obtained 138 sample of permanent employees at PT. PLN (Persero) in the cities of Banda Aceh and Aceh Besar. The data used is primary data collected in a hybrid way, that is, some of the questionnaires were answered directly and some were answered through the google form. This study using multiple linear regression models and moderated regression analysis. The results of this study indicate that both simultaneously and partially, ethical awareness and ethical judgement have a significant effect on whistleblowing, but the results of testing the moderating variable, namely emotion, cannot moderate ethical awareness and ethical considerations on whistleblowing.